Rodent Models to Analyze the Glioma Microenvironment - Hetze, Susann (ASN Neuro, 2021)
Animal models are still indispensable for understanding the basic principles of glioma development and invasion. Preclinical approaches aim to analyze the treatment efficacy of new drugs before translation into clinical trials is possible. Various animal disease models are available, but not every approach is useful for addressing specific questions. In recent years, it has become increasingly evident that the tumor microenvironment plays a key role in the nature of glioma. In addition to providing an overview, this review evaluates available rodent models in terms of usability for research on the glioma microenvironment.